2008
DOI: 10.1002/jcu.20544
|View full text |Cite
|
Sign up to set email alerts
|

The chorionic bump in an ectopic pregnancy

Abstract: The chorionic bump, an irregular, convex bulge of the choriodecidual surface into the gestational sac (GS), is a recently described, uncommon abnormality of the 1st-trimester GS and is associated with a guarded prognosis for early pregnancy. The case of this 42-year-old female demonstrates a previously unreported relationship: a transvaginal sonographic finding of a chorionic bump associated with a spontaneous tubal ectopic pregnancy. This might support the hypothesis that the chorionic bump represents a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The exact etiology of a chorionic bump is unknown, but it is thought to be most likely a hematoma, as the echogenicity of the bump changes to become more echogenic over time and has the signal characteristics typical of hemorrhage on magnetic resonance imaging. Histological examination of the conceptus after spontaneous miscarriage also supports this hypothesis. A chorionic bump is an entity different from a subchorionic hematoma, which is the presence of echolucent fluid (blood) between the uterine wall and the chorion or within the endometrial cavity (Figure c).…”
Section: Introductionmentioning
confidence: 95%
“…The exact etiology of a chorionic bump is unknown, but it is thought to be most likely a hematoma, as the echogenicity of the bump changes to become more echogenic over time and has the signal characteristics typical of hemorrhage on magnetic resonance imaging. Histological examination of the conceptus after spontaneous miscarriage also supports this hypothesis. A chorionic bump is an entity different from a subchorionic hematoma, which is the presence of echolucent fluid (blood) between the uterine wall and the chorion or within the endometrial cavity (Figure c).…”
Section: Introductionmentioning
confidence: 95%
“…After the late first‐trimester period, the possibility of fetal demise or pregnancy loss later on in pregnancy decreases dramatically, especially in fetuses with no abnormal findings on scan . The incidental reported association with ectopic pregnancy, fetal malformations such as acrania or forearm reduction defect, and chromosomal abnormalities were also absent from our series, although one of our fetuses had trisomy 21.…”
Section: Discussionmentioning
confidence: 61%
“…Several factors can explain this difference. First, previous studies were based on earlier pregnancies from a largely heterogenous population, which included a significant number of cases with an anembryonic sac, an embryo without detectable heartbeat, or even an ectopic pregnancy . Obviously, in this setting, the possibility for poor pregnancy outcome is very high.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent case report of a chorionic bump in a tubal ectopic pregnancy was offered in support of this premise, considering the association of hemorrhage with ectopics. However, no pathologic correlate of the bump was identified . In a case of first‐trimester embryonic demise associated with multiple chorionic bumps, the authors concluded that findings of hemorrhage on histopathologic examination of the aborted tissue suggested that hematomas were the source of the bumps .…”
Section: Discussionmentioning
confidence: 99%